Localized downcore variation of microbial profiles in mangrove sediments and its role in blue carbon storage - Nurul Aqeela,; Nur Hidayah,; Nabilah Khairi,; Nur Hazlin Hazrin-Chong,; Mohammad Rozaimi, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The profiling of the composition and diversity of microbial communities in mangrove sediments allow for the understanding of blue carbon storage. This study investigated the downcore variation of microbial profiles and related carbon fixation pathways in mangrove sediments of Pulau Seribuat, Malaysia. 16s RNA sequencing was carried out on replicate cores in three depth layers. The bacterial phyla of Proteobacteria, Chloroflexi and Planctomycetota showed significant downcore variation within the sediment depths. Proteobacteria showed highest abundance in the top layer while Chloroflexi dominated the bottom layer. Statistical analysis indicated that Proteobacteria and Chloroflexi abundance were both significantly different between top and bottom layers, while the middle layer acted as a transition zone for the microbial community. Further analysis of predicted functional pathways indicated the prevalence of the Calvin-Benson-Bassham (CBB) cycle and the reverse tricarboxylic acid (rTCA) cycles throughout the three sediment layers. Although trends were observed in their abundance, the PERMANOVA tests showed no significant differences. These findings suggest that sediment microbial profile is influenced by other factors such as oxygen and nutrient availability, which in turn may affect the rates of carbon fixation. This suggests that the microbial community composition may serve as a potential indicator for processes within the blue carbon cycle, aiding in management of these ecosystems.